Handbook of Atopic Eczema - Ring, Johannes; Przybilla, Bernhard; Ruzicka, Thomas; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2006)
Atopic eczema (atopic dermatitis, neurodermitis diffusa, endogenous eczema) is one of the most common skin diseases of our time and is still increasing in prevalence dramatically all over the world. The reasons for this increase are not known. It occurs at any age, not only in childhood, approximately 2/3 of children affected will suffer from this disease when they are grown-up. Written by leading experts of their field, this second edition comprises the state of the art in pathophysiology, clinical medicine and therapeutic management. It demonstrates that there is no simple "miracle" cream, pill or diet for this disease, but that a disturbed barrier function can only be repaired by adequate and individualized skin care and it shows how unspecific anti-inflammatory treatment has to be individually tailored according to body area affected, patient age and acuity of skin lesions. All physicians will find this book most helpful in the painstaking search for the individual causal or eliciting factors.
Atopy: Condition, Disease, or Syndrome? -- The History of Atopic Eczema/Dermatitis -- Epidemiology of Atopic Eczema -- The Burden of Atopic Eczema -- Clinical Symptoms of Atopic Eczema -- Atopic Eczema in Infants -- Stigmata of the Atopic Constitution auB. Przybilla -- Minimal Variants of Atopic Eczema -- Diagnosis of Atopic Eczema -- Differential Diagnosis of Atopic Eczema -- Respiratory Symptoms in Atopic Eczema — Focus on Asthma and Early Treatment -- Complications and Diseases Associated with Atopic Eczema -- Diseases Rarely Associated with Atopic Eczema -- Natural History of Atopic Eczema -- Dry Skin -- Occupational Aspects of Atopic Eczema with Emphasis on Atopic Hand Eczema -- Allergic Contact Dermatitis and Atopic Eczema -- Immunodeficiency Syndromes and Atopic Eczema -- Atopic Diseases in Families -- Histopathologic and Ultrastructural Aspects of Atopic Eczema -- Pathophysiology and Clinical Manifestation of Itch in Atopic Eczema -- Clinical Basics of Atopic Eczema: Synopsis -- Clinical Genetics of Atopic Eczema -- The Molecular Genetics of Atopy -- Genetics of Atopic Eczema -- Mechanisms of IgE-Regulation -- Dendritic Cells in Atopic Eczema -- Inflammatory Dendritic Epidermal Cells -- Extrinsic and Intrinsic Atopic Eczema -- Mast Cells in the Skin -- The Role of Eosinophils in Atopic Eczema -- Role of T Cells in Atopic Eczema -- Keratinocytes in Atopic Eczema -- Inflammatory Mediators and Chemokines in Atopic Eczema -- Cytokines in Atopic Dermatitis (Eczema) -- Neuropeptides and Atopic Eczema -- Epidermal Lipids in Atopic Eczema -- The Phenomenon of Irritable Skin in Atopic Eczema -- Environmental Pollution and Atopic Eczema -- The Role of Inhalant Allergens in Atopic Dermatitis -- Role of Food Allergy in Atopic Eczema -- Staphylococcus aureus and Atopic Eczema -- Animal Models of Atopic Eczema -- Autoantibodies in Atopic Eczema -- Pathophysiology of Atopic Eczema: Synopsis -- Primary Prevention of Atopy -- Role of Allergy Testing in Atopic Eczema -- Probiotics in Atopic Eczema -- Measuring Disturbed Barrier Function in Atopic Eczema -- Basic Topical Therapy with Emollients in Atopic Eczema -- Syndets in the Treatment of Atopic Eczema -- Topical Treatment with Glucocorticoids -- Antimicrobial Therapy in Atopic Eczema -- Antihistamines in Atopic Eczema -- Climatotherapy in Atopic Eczema -- Skin Care in Atopic Eczema -- Dietary Management of Atopic Eczema -- Phototherapy for Atopic Eczema -- Atopic Eczema — Psychosomatic and Psychobiological Aspects -- Phosphodiesterase 4 Inhibitors for Atopic Eczema -- Music Therapy in Atopic Eczema -- Topical Immunomodulators in the Treatment of Atopic Eczema -- Eczema School: Practical Approaches in an Efficient Module of Tertiary Prevention Programs -- Unconventional Treatments in Atopic Eczema -- Alternative Medicine for Atopic Eczema: A Comment -- Therapy of Atopic Eczema: Synopsis.
Keywords: Dermatology; Allergy; Immunology; Occupational medicine; Dermatology; Allergology; Immunology; Occupational Medicine/Industrial Medicine